Practice applications of research. Appraisal and coping with vaso-occlusive crisis in adolescents with sickle cell disease. - Fletcher C (Pediatric Nursing)
Purpose: To explore the relationships among appraisals of vaso-occlusive events, coping behavior during the event, and adjustment in adolescents with sickle cell disease. Method: A descriptive, correlation design used a purposive sample of 68 adolescents with sickle cell disease. Three questionnaires were used to collect the data: Pain Beliefs and Perceptions Inventory (PBPI), Coping Strategies Questionnaire (CQS), and a demographic questionnaire. Correlation and multiple regression were used to analyze the data. Findings: Appraisal factors positively correlated with coping strategies and adjustment. Multiple regression found that appraisal of the event as catastrophic predicted the reinterpretation of pain sensations (p < .001). Conclusions: Adolescents with more negative thoughts during vaso-occlusion crisis used ineffective coping strategies and reported poorer adjustment.